Postcolonial migrations in Russia: the racism, informality and discrimination nexus. Issue 1 (11th March 2019) - Kuznetsova, Irina; Round, John
Abstract : Purpose: The purpose of this paper is to contribute to the challenges of bringing postcolonial, racism and migration research into a meaningful dialogue. Based on the research examining migration from Central Asia into Russia, the paper analyses migration policy and the everyday experiences of migrants. Design/methodology/approach: The paper is based on mixed methodologies, including narrative, semi-structured and in-depth interviews with migrants from Uzbekistan, Tajikistan and Kyrgyzstan in Russian cities and those who returned to their country of origin (over 300 people), interviews with representatives of NGOs, state officials and journalists in 2013–2016 and an analysis of the legislation and mass-media regarding migration from Central Asia. Findings: The paper demonstrates that experiencing racism is a part of everyday life for migrants from Central Asia living in Russia. Whether this is in interactions with the state, fear of persecution on the street by the police or in the workplace, it is a constant factor. It argues that the political and everyday xenophobia and racism demonstrates deeply rooted imperial views in Russia's inner politics and shapes attitudes toward migrants. Social implications: The paper contributes to broader debates on the linkages between migration and racism in Europe, in particularly questioning the positionality of migrants from "not-European" countries. Originality/value: Mbembe's approach to "let die" is pertinent in understanding postcolonial migration. Racism continually plays a role in "normalization" of abuse toward migrants and restrictive migration policy. Blaming "the migrant" for acting informally, draining healthcare resources and for posing a security risk provides a much-needed scapegoat for the state.